2017
DOI: 10.1039/c6an00567e
|View full text |Cite
|
Sign up to set email alerts
|

Orientational binding modes of reporters in a viral-nanoparticle lateral flow assay

Abstract: Using microscopy and image analysis, we characterize binding of filamentous viral nanoparticles to a fibrous affinity matrix as models for reporter capture in a lateral flow assay (LFA). M13 bacteriophage (M13) displaying an in vivo-biotinylated peptide (AviTag) genetically fused to the M13 tail protein p3 are functionalized with fluorescent labels. We functionalize glass fiber LFA membranes with antibodies to M13, which primarily capture M13 on the major p8 coat proteins, or with avidin, which captures M13 at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…Biotinylated Fluor-phage were imaged in capillary-driven transport through the membrane using a sCMOS camera (pco.edge 4.2, 30 frame sec -1 , 30 ms exposure time, 208.3 μm × 213 μm image field of view). The position of the fluid interface scaled as the square root of time, 30 following Washburn's equation. 32 Recording began immediately after liquid breakthrough in the field of view ( t = 0 sec) and ceased when the phage particles exhibited only Brownian (rather than advective) motion, typically after six minutes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biotinylated Fluor-phage were imaged in capillary-driven transport through the membrane using a sCMOS camera (pco.edge 4.2, 30 frame sec -1 , 30 ms exposure time, 208.3 μm × 213 μm image field of view). The position of the fluid interface scaled as the square root of time, 30 following Washburn's equation. 32 Recording began immediately after liquid breakthrough in the field of view ( t = 0 sec) and ceased when the phage particles exhibited only Brownian (rather than advective) motion, typically after six minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we showed that the flow field within an LFA membrane couples to the phage shape and promotes reorientation for binding, and hypothesized that binding efficiency can be increased by tuning the size and shape of reporters. 30 …”
Section: Introductionmentioning
confidence: 99%
“…As of March 2020 we did not find any scientific manuscript describing the development of a LFA using solely Fusion5, instead we found references using Fusion5 as part of LF strips or more complex structures. [172][173][174][175][176][177][178][179] Non-conventional materials. Other interesting low cost alternatives to the conventional LFAs membranes, such as cotton threads, cellulose and glass capillaries have been described in the last years.…”
Section: Assembly Of the Lfamentioning
confidence: 99%
“…The benefits of oriented binding of antibodies to magnetic nanoparticles through modification of antibodies' carbohydrate components were shown by Puertas et al using the example of LFIA for choriogonadotropin [46]. A comparison of methods of immobilization for receptors in bacteriophage-based LFIA is given in the works of Kim et al [47,48]. In particular, article [48] discussed the use of in vivo-biotinylated peptide for oriented immobilization of receptor molecules on a test strip.…”
Section: Proper Receptor For Lfiamentioning
confidence: 99%
“…A comparison of methods of immobilization for receptors in bacteriophage-based LFIA is given in the works of Kim et al [47,48]. In particular, article [48] discussed the use of in vivo-biotinylated peptide for oriented immobilization of receptor molecules on a test strip.…”
Section: Proper Receptor For Lfiamentioning
confidence: 99%